Factors affecting the solvency of agricultural cooperatives in Vinh Long province - Na, Vo Thi Van; Cuong, Ngo Cao (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
This study has identified the factorsfactors affecting the solvency of agricultural cooperatives in Vinh Long province, Vietnam. This study conducted surveys of 626 farmers and filtered out 297 farmers who are currently in debt to credit institutions and whose payments are not due or have been paid within 12 months. Multivariable linear regression method was used to determine factors affecting solvency of agricultural cooperatives in Vinh Long province. Based on the data, binary logistic was used for research. SPSS ver26 was used to measure the factors including age, educational level, size of farm, farm income, natural disasters - epidemics, interest rate to the solvency of agricultural cooperatives. The result of the study indicates that educational level, size of farm, farm income significantly affected the solvency of agricultural cooperatives. The results show five factors affecting the solvency of agricultural cooperatives in Vinh Long province, Vietnam, including three positive factors, two negative factors of the six initially factors of the research model. This result provides the basis for lenders to have a realistic view of their loan repayment effectiveness, and to adopt appropriate policies and practices to mitigate risk during operation. On the other hand, it can also help local, state, and local macro managers to adopt appropriate policies, implement poverty alleviation programs and ensure social security.